Pengaruh Sistem Pengukuran Kinerja dan Penghargaan Terhadap Kinerja Karyawan Dengan Organizational Citizenship Behavior Sebagai Variabel Mediasi Di PT. Perkebunan Nusantara IV Medan - Rizka, Intan Novia; Tahura, T. Lyza; Suyar, Annisa Suvero (Yayasan Cita Cendekiawan Al Khwarizmi, 2022)
This study aims to determine the effect of performance measurement and rewardsystems on employee performance with Organizational Citizenship Behavior (OCB) as a mediating variable at PT. Perkebunan Nusantara IV Medan. In this study using the associative method with a quantitative approach. The total population in the study was 368 people and a sample of 79 respondents using proportional random sampling. The analysis technique used is multiple linear regression and path analysis. The results showed that the variables of the performance measurement system, rewards, and organizational citizenship behavior (OCB) had a positive and significant effect on employee performance. The performance measurement system and rewards has a positive and significant effect on employee performance through organizational citizenship behavior (OCB) as a mediating variable.